2016
DOI: 10.1007/s11764-016-0519-6
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and frailty in older adults: a nested case-control study of the Mexican Health and Aging Study

Abstract: Purpose Understanding how the convergence between chronic and complex diseases—such as cancer—and emerging conditions of older adults—such as frailty—takes place would help in halting the path that leads to disability in this age group. The objective of this manuscript is to describe the association between a past medical history of cancer and frailty in Mexican older adults. Methods This is a nested in cohort case-control study of the Mexican Health and Aging Study. Frailty was categorized by developing a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 30 publications
3
29
0
1
Order By: Relevance
“…The development of frailty among cancer survivors has been documented in earlier studies, which propose that a possible pathophysiology could be iatrogenic damage and residual chronic conditions as the result of cancer and biological aging, leading to clinical expression of frailty 17,18. This study found that two or more nonelective admissions over the past 12 months increased the risk of developing frailty.…”
Section: Discussionsupporting
confidence: 61%
“…The development of frailty among cancer survivors has been documented in earlier studies, which propose that a possible pathophysiology could be iatrogenic damage and residual chronic conditions as the result of cancer and biological aging, leading to clinical expression of frailty 17,18. This study found that two or more nonelective admissions over the past 12 months increased the risk of developing frailty.…”
Section: Discussionsupporting
confidence: 61%
“… 12 In addition to preexisting frailty, cancer and its treatments present additional stressors that can accelerate aging and worsen frailty status. 5 , 7 , 13 , 14 , 15 Understanding the association of frailty and change in frailty status with cancer diagnosis and subsequent mortality is important for optimal selection of cancer treatments and survivorship care. 3 , 4 Despite the dynamic nature of frailty, to our knowledge, no prior study has examined whether changes in functional decline over time are associated with cancer mortality.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that we only considered history of cancer in our study, while patients carrying active malignancies during the last 24 months before enrollment were excluded. Nevertheless, older cancer survivors may be more likely to develop frailty or worsening of the health status, and such association may be especially relevant among individuals with a recent (< 10 years) history of cancer [35].…”
Section: Discussionmentioning
confidence: 99%